Discards of the trawl and long line Spanish fleets in ICES Subarea VII in 1994 - Pérez-Contreras, María Nélida; Trujillo-Gorbea, Valentín; Pereda, Pilar (1996)
Within the framework of a European Union (UE) contract and with voluntary participation of commercial fishing vessels, a discard sampling programme based on stratified random sampling by fisheries covered the activities of trawl and long line Spanish fleets fishing in ICES Subarea VII in 1994. Discards of commercial and non-commercial species, including species of pinnipeds, cetaceans, sea turtles and sea birds, caught incidentally were estimated in kg per fishing hour by ICES rectangle and depth stratum in 1994. The sampling programme was carried out by observers on board commercial fishing vessels during normal fishing activity. A total of 238 species caught by trawlers and 76 by long liners were determined. The comparison of the two fleets regarding their ratios of discards in 1994 shows that the larger percentages of discards relative to total catches are found in the trawl fisheries (48%) and around 50% are primarily due to the discards of three species of fish and one of crustacea. Seasonal variation in the case of discards of the two main species (Great Silver Smelt and Horse Mackerei) was observed. The depth at which discards were hig lies between 200 and 400m. Conversely, long line fishing in Subarea VII shows a lower discard rate than that of trawlers (10%). Approximately 60% of discards primarily comprise two species of fish, Blue Whiting and Great Silver Smelt, both of which show the highest discard value per f.h. in the 3rd quarter. No differences were observed by depth strata.